Authentic Leadership Ketua Remaja Mushola Baiturrahim Taman Sidoarjo - Nur Aini, Anisah (Tanzhim: Jurnal Dakwah Terprogram, 2023)
Abstract: Da'wah managers are responsible for mobilizing and coordinating human resources, one of which is by using leadership. As a leader who is considered to have abilities beyond his members, with this ability the leader is trusted and is expected to be able to mobilize and coordinate human resources. However, the reality on the ground for da'wah managers within the scope of youth prayer leaders, is faced with the problem that the chairman's self-readiness to lead is not ready to use. Still need improvement and polishing of one's ability to be ready to face organizational dynamics in leading young mushola. In the midst of the limitations of the application of leadership design. Then the leadership design is applied in the context of this situation by using Authentic Leadership theory. Authentic Leadership provides an overview of the implementation of leadership by implementing the best version of the leader (chairman Remus) by maintaining the integrity that he already has. Application in this context, provides an overview of the plan, things that need to be prepared and fulfilled to show the best quality according to the Authentic Leadership version. Keywords: Authentic Leadership